Ultrathin barrier film and preparation method thereof

By improving the equipment structure, raw materials and processes, an ultra-thin barrier film with an oxygen transmittance of less than 10cm3/m2·24h was prepared, which solved the problem that the barrier film thickness was difficult to further thin in the prior art, and achieved cost reduction and performance improvement.

CN119820957APending Publication Date: 2025-04-15XINLE HUABAO HYGIENE MATERIALS TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411958718.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art cannot further thin the barrier packaging film, resulting in high production costs and cannot meet the product needs of high oxygen transmittance.

Method used

By improving the equipment structure, raw materials and processes, the material layers of PE layer/adhesive layer/barrier layer/adhesive layer/PE layer are laminated layer by layer, combined with casting process and multi-layer co-extrusion process, an ultra-thin barrier film with an oxygen transmittance of less than 10cm3/m2·24h was prepared.

Benefits of technology

It is achieved that the thickness of the barrier film is reduced by about 25%-30%, reduce production costs, and maintain the film's elongation and traction performance while meeting the barrier performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216553360000041
    Figure BDA0005216553360000041
  • Figure BDA0005216553360000051
    Figure BDA0005216553360000051
  • Figure BDA0005216553360000052
    Figure BDA0005216553360000052
Patent Text Reader

Abstract

The invention belongs to the technical field of barrier film preparation, and particularly relates to an ultrathin barrier film, a PE layer of the ultrathin barrier film comprises the following components in parts by mass: 10-20 parts of LDPE, 35-45 parts of LLDPE, 40-50 parts of HDPE and 2-8 parts of color master batch; the bonding layer comprises maleic anhydride, and the melt index of the maleic anhydride is 0.4-0.6 g / 10 min; the barrier layer comprises an ethylene-vinyl alcohol copolymer, and the content of vinyl alcohol in the ethylene-vinyl alcohol copolymer accounts for 36-42%. By simultaneously improving the equipment structure, the raw materials and the process, the thickness of the prepared ultrathin barrier film is reduced on the premise that the oxygen permeability is lower than 10cm < 3 > / m < 2 >. 24h, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of barrier film preparation, and particularly relates to an ultra-thin barrier film and a preparation method thereof. Background Art

[0002] The food packaging films currently on the market require an oxygen permeability barrier of 10 cm 3 / m 2 Less than 24 hours. For some products with volatile odors, such as scented daily necessities, in order to ensure that the effective ingredients of the fragrance are fully retained before use and not volatilized too much, the oxygen permeability is required to reach a level of more than 10, so that the volatile fragrance can be fully felt after opening the packaging film during use.

[0003] In the prior art, the barrier packaging film produced by the blown film process has a thickness of 3-4 filaments (1 filament equals 10 microns), and has a very good barrier effect, far exceeding the product requirements. However, in order to reduce costs, it needs to be thinned. However, current technology cannot achieve further thinning, and can only maintain the use of this high-cost thick film. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides an ultra-thin barrier film and a preparation method thereof. By improving the equipment structure, raw materials and process at the same time, the prepared ultra-thin barrier film has an oxygen permeability of less than 10cm 3 / m 2 ·The thickness is reduced under the premise of 24 hours, which reduces the production cost.

[0005] The specific technical solution adopted by the present invention is:

[0006] An ultra-thin barrier film is formed by laminating the following material layers layer by layer: PE layer / adhesive layer / barrier layer / adhesive layer / PE layer, and the weight proportions of each layer are 38-43:3-7.5:8-12:3-7.5:38-43 respectively.

[0007] The PE layer comprises, by weight, 10-20 parts of LDPE, 35-45 parts of LLDPE, 40-50 parts of HDPE, and 2-8 parts of masterbatch;

[0008] The adhesive layer comprises maleic anhydride, and the melt index of the maleic anhydride is 0.4-0.6 g / 10 min;

[0009] The barrier layer comprises ethylene-vinyl alcohol copolymer, wherein the content of vinyl alcohol in the ethylene-vinyl alcohol copolymer is 36-42%.

[0010] Furthermore, the adhesive layer also includes metallocene polyethylene. The adhesive layer includes 35-45 parts of maleic anhydride and 55-65 parts of metallocene polyethylene by weight.

[0011] Furthermore, the melt index of the metallocene polyethylene is 1-2 g / 10 min.

[0012] A method for preparing an ultrathin barrier film comprises the following steps:

[0013] S1. Prepare raw materials according to the ratio of each material layer;

[0014] S2, using cast film multi-layer co-extrusion process, adding adhesive layer raw materials to the A machine of the screw extruder, adding barrier layer raw materials to the B machine, and adding PE layer raw materials to the C and D machines;

[0015] S3, start machine B, machine C, and machine D to generate a barrier layer and two PE layers respectively;

[0016] S4. After the barrier layer and the PE layer are leveled, start the A machine to generate an adhesive layer, and laminate the material layers according to the order of PE layer / adhesive layer / barrier layer / adhesive layer / PE layer to form an ultra-thin barrier film.

[0017] Furthermore, the screw extruder is a 4-screw 5-layer extruder structure or a 5-screw 5-layer extruder structure.

[0018] Furthermore, the temperature of the screw extruder A is 200-280°C, the temperature of the screw extruder B is 190-250°C, the temperature of the screw extruder C is 180-270°C, the temperature of the screw extruder D is 180-270°C, and the extrusion die head temperature of the screw extruder is 255-265°C.

[0019] Furthermore, the film thicknesses of the C machine, A machine, B machine, A machine, and D machine are 9.5-10.75 μm, 0.75-1.875 μm, 2-3 μm, 0.75-1.875 μm, and 9.5-10.75 μm, respectively.

[0020] Furthermore, the screw length-to-diameter ratios of the screw extruders A and B are both 30-32:1, and the screw compression ratios are both 2-3.

[0021] The beneficial effects of the present invention are:

[0022] 1. The final thickness of the ultra-thin barrier film of the present invention is 2.5 microns, and the oxygen permeability is 9 cm 3 / m 2 After 24 hours, the barrier layer of the barrier film only accounts for 8% and is only 0.2 microns thick. It can be seen that the ultra-thin barrier film of the present invention reduces the thickness of the ultra-thin barrier film by about 25%-30% while meeting the barrier performance requirements, thereby greatly reducing the production cost.

[0023] 2. The purpose of reducing the A / B flow channel in the present invention is to reduce the flow rate by reducing the flow channel, rather than reducing the flow rate by the rotation speed of the screw, so as to ensure the rotation speed of the screw to ensure the plasticizing performance.

[0024] 2. The ultra-thin barrier film of the present invention improves the equipment structure, raw materials and process during the preparation process, so that the prepared ultra-thin barrier film has an oxygen permeability of less than 10cm 3 / m 2 ·The thickness is reduced within 24 hours.

[0025] First of all, the traditional preparation of ultra-thin barrier films usually adopts the blown film method, but the thickness distribution of the film prepared by the blown film method is poor. When the thickness of the barrier packaging film is further reduced, it is easy to break. Although the film prepared by the cast film method has a more uniform thickness, its extensibility is poor, and it is difficult to further reduce the thickness of the barrier film.

[0026] Therefore, the present invention improves the screw structure of the screw extruder of the cast film method. The screw length-to-diameter ratio of the traditional screw structure should not be too large to avoid increasing the residence time of the material at high temperature. Some polymers with poor thermal stability will cause thermal decomposition. Therefore, the traditional screw length-to-diameter ratio is generally 20-27:1. However, the screw structure of the barrier layer and the bonding layer in the present invention has a length-to-diameter ratio of 30-32:1, which is conducive to material mixing and plasticization, so that the film maintains good extensibility after thinning, and is suitable for traction. In order to solve the problem that the screw length-to-diameter ratio of the screw structure should not be too large, while improving the screw structure, it is also necessary to improve the raw materials. The bonding layer uses maleic anhydride prepolymer with a high melt index, and the barrier layer uses ethylene-vinyl alcohol copolymer with high thermal stability. The improvements in the equipment structure, raw materials and processes in the present invention are complementary and inseparable. The improved equipment structure is combined with the specific raw materials in the present invention, and the process parameters are adjusted to finally achieve the improvement of the ultra-thin barrier film in the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. 1. Specific embodiments

[0029] Example 1

[0030] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 32:1, and the screw compression ratio is 2;

[0031] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0032] 3. Raw materials: PE layer: 15 parts of LDPE, 40 parts of LLDPE, 45 parts of HDPE, 5 parts of masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.5g / 10min.

[0033] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0034] 4. Product structure and formula

[0035]

[0036] Example 2

[0037] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 32:1, and the screw compression ratio is 2;

[0038] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0039] 3. Raw materials: PE layer: 15 parts of LDPE, 40 parts of LLDPE, 45 parts of HDPE, 5 parts of masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.5g / 10min.

[0040] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0041] 4. Product structure and formula

[0042]

[0043] Example 3

[0044] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 32:1, and the screw compression ratio is 2;

[0045] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0046] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: 40 parts maleic anhydride prepolymer with a melt index of 0.5g / 10min, 60 parts metallocene polyethylene with a melt index of 1g / 10min;

[0047] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0048] 4. Product structure and formula

[0049]

[0050] Example 4

[0051] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 32:1, and the screw compression ratio is 2;

[0052] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0053] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: 40 parts maleic anhydride prepolymer with a melt index of 0.5g / 10min, 60 parts metallocene polyethylene with a melt index of 1.5-2g / 10min;

[0054] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0055] 4. Product structure and formula

[0056]

[0057] Example 5

[0058] 1. Equipment: A screw extruder with a 5-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the A, E and B screw extruders is 32:1, and the screw compression ratio is 2;

[0059] 2. Process parameters: A / E machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0060] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: 40 parts maleic anhydride prepolymer with a melt index of 0.5g / 10min, 60 parts metallocene polyethylene with a melt index of 1.5-2g / 10min;

[0061] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0062] 4. Product structure and formula

[0063]

[0064] Comparative Example 1

[0065] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 25:1, and the screw compression ratio is 3;

[0066] 2. Process parameters: A machine temperature: 200-260℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0067] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.1g / 10min.

[0068] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0069] 4. Product structure and formula

[0070]

[0071] Comparative Example 2

[0072] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 25:1, and the screw compression ratio is 3;

[0073] 2. Process parameters: A machine temperature: 200-240℃; B machine temperature 190-220℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0074] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.1g / 10min.

[0075] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0076] 4. Product structure and formula

[0077]

[0078]

[0079] Comparative Example 3

[0080] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 25:1, and the screw compression ratio is 3;

[0081] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0082] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.1g / 10min.

[0083] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0084] 4. Product structure and formula

[0085]

[0086] Comparative Example 4

[0087] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 25:1, and the screw compression ratio is 3;

[0088] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0089] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.5g / 10min.

[0090] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0091] 4. Product structure and formula

[0092]

[0093] Comparative Example 5

[0094] 1. Equipment: A screw extruder with a 4-screw 5-layer extrusion structure is used. The screw length-to-diameter ratio of the screw extruder A and the screw extruder B is 32:1, and the screw compression ratio is 2;

[0095] 2. Process parameters: A machine temperature: 200-280℃; B machine temperature 190-250℃; C / D machine temperature: 180-270℃; extrusion die head temperature: 260℃;

[0096] 3. Raw materials: PE layer: 15 parts LDPE, 40 parts LLDPE, 45 parts HDPE, 5 parts masterbatch; Adhesive layer: maleic anhydride prepolymer with a melt index of 0.1g / 10min.

[0097] Barrier layer: ethylene-vinyl alcohol copolymer, wherein the vinyl alcohol content is 36-42%;

[0098] 4. Product structure and formula

[0099]

[0100] 2. Performance Test

[0101] According to the preparation methods in Examples 1-5 and Comparative Examples 1-5, barrier films were prepared respectively, and then the performance of each group of barrier films was tested. The test results are shown in Tables 1 and 2.

[0102] Table 1

[0103]

[0104]

[0105] Table 2

[0106]

Claims

1. A method for preparing an ultra-thin barrier film, wherein the ultra-thin barrier film is formed by laminating the following material layers layer by layer: PE layer / adhesive layer / barrier layer / adhesive layer / PE layer, characterized in that: The mass proportions of each layer are 38-43:3-7.5:8-12:3-7.5:38-43; The PE layer comprises, by weight, 10-20 parts of LDPE, 35-45 parts of LLDPE, 40-50 parts of HDPE, and 2-8 parts of masterbatch; The adhesive layer comprises maleic anhydride, and the melt index of the maleic anhydride is 0.4-0.6 g / 10 min; The barrier layer comprises ethylene-vinyl alcohol copolymer, wherein the content of vinyl alcohol in the ethylene-vinyl alcohol copolymer is 36-42%; The method for preparing an ultra-thin barrier film comprises the following steps: S1. Prepare raw materials according to the ratio of each material layer; S2, using cast film multi-layer co-extrusion process, adding adhesive layer raw materials to the A machine of the screw extruder, adding barrier layer raw materials to the B machine, and adding PE layer raw materials to the C and D machines; S3, start machine B, machine C, and machine D to generate a barrier layer and two PE layers respectively; S4. After the barrier layer and the PE layer are leveled, start the A machine to generate an adhesive layer, and laminate the material layers according to the order of PE layer / adhesive layer / barrier layer / adhesive layer / PE layer to form an ultra-thin barrier film.

2. The method for preparing an ultra-thin barrier film according to claim 1, characterized in that: The adhesive layer further comprises metallocene polyethylene. The adhesive layer comprises 35-45 parts of maleic anhydride and 55-65 parts of metallocene polyethylene by weight.

3. The method for preparing an ultra-thin barrier film according to claim 1, characterized in that: The melt index of the metallocene polyethylene is 1-2 g / 10 min.

4. The method for preparing an ultra-thin barrier film according to claim 1, characterized in that: The screw extruder is a 4-screw 5-layer extruder structure or a 5-screw 5-layer extruder structure.

5. The method for preparing an ultra-thin barrier film according to claim 1, characterized in that: The temperature of the screw extruder A is 200-280°C, the temperature of the screw extruder B is 190-250°C, the temperature of the screw extruder C is 180-270°C, the temperature of the screw extruder D is 180-270°C, and the extrusion die head temperature of the screw extruder is 255-265°C.

6. The method for preparing an ultra-thin barrier film according to claim 1, characterized in that: The film thicknesses of the C machine, A machine, B machine, A machine, and D machine are 9.5-10.75 μm, 0.75-1.875 μm, 2-3 μm, 0.75-1.875 μm, and 9.5-10.75 μm, respectively.

7. The method for preparing an ultra-thin barrier film according to claim 1, characterized in that: The screw length-to-diameter ratios of the screw extruders A and B are both 30-32:1, and the screw compression ratios are both 2-3.

Citation Information

Patent Citations

  • Environmentally-friendly high-barrier film used for composite all-plastic flexible tubes, and preparation method thereof

    CN109927357A

  • PE multilayer barrier composite film and preparation method thereof

    CN112677599A

  • High-barrier hose packaging composite sheet and preparation method thereof

    CN115195244A

  • High-barrier PE film with antibacterial function and preparation method thereof

    CN115257107A

  • High-barrier easy-to-tear composite film and preparation method thereof

    CN116061528A